Outcomes Following Left Ventricular Assist Device Exchange: Focus on the Impacts of Device Infection. Issue 6 (15th October 2020) - Yost, Gardner; Coyle, Laura; Gallagher, Colleen; Cotts, William; Pappas, Patroklos; Tatooles, Antone
Abstract : Supplemental Digital Content is available in the text. Abstract : Hemodynamic support with continuous-flow left ventricular assist device (CF-LVAD) therapy has proven a reliable treatment for advanced heart failure. Although modern LVADs are highly durable, device failure and infection can be resolved with surgical exchange of pump components. In this study, we investigated the incidence and outcomes of LVAD exchange with the HeartMate II and HeartWare HVAD. Data were obtained from 677 patients who underwent CF-LVAD implantation between 2005 and 2016. Patients who underwent a device exchanged were included. The primary outcomes were length of hospital stay and mortality. Of the 677 patients included in this study, 72 (10.6%) required LVAD exchange. Thirty-day and 1-year mortality rates were comparable to primary LVAD implantation: 4.3% vs. 3.49%, p = 0.727 and 20.3% vs. 20.7%, p = 0.989, respectively. Thirty-one patients (4.5%) underwent exchange with ongoing infection. Kaplan–Meier analysis indicated significant differences in survival between groups based on indication for exchange. Patients who underwent exchange after more than 150 days of active infection suffered worse postexchange survival than those who underwent exchanged earlier ( P = 0.007). While exchange was required only in 10.6% of patients undergoing LVAD implantation, our results show device exchange may be executed safely and effectively, with long-term outcomes similar to primary LVAD implantation. The indication for device exchange impacts postexchange outcomes, and those exchanged with LVAD infection tend to fare worse than those exchanged for device malfunction or thrombus. Patients who are exchanged with active infection have better postoperative survival if the exchange is performed expeditiously after medical management has failed.